Innovation Efficiency and the Spatial Correlation Network Characteristics of Intelligent-Manufacturing Enterprises - Ningning Fu (Complexity)
A data envelopment analysis cross-efficiency model was used to measure the innovation efficiency of Chinese intelligent-manufacturing (IM) enterprises. This paper took as samples the number of granted patents and R&D investments of IM enterprises listed from 2015 to 2020. This research used the modified gravity model to determine the innovation efficiency and the spatial correlation of IM enterprises in China and used UCINET software to reveal the innovation efficiency and spatial network characteristics of IM enterprises through a social network analysis. The study found that the relationship was significant and frequently close between innovation efficiency and the spatial correlation network of IM enterprises. The distribution of the spatial association network was “core-edge,” and IM enterprises in Eastern China were at the network core and mostly played an intermediary role. The spatial correlation network had four modules. The distribution of the enterprise innovation correlation was uneven within each module, amalgamation was poor among the subgroups, and characteristics of highly cohesive subgroups were present.